2017
DOI: 10.1038/gt.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve as a delivery vector of IL-24 gene therapy for head and neck squamous cell carcinoma in vivo

Abstract: Beneficial bacteria are becoming ever more popular gene delivery method for hypoxia-tumor targeting in vivo. In this study we investigated the therapeutic effect of new recombinant Bifidobacterium breve strain expressing interleukin (IL)-24 gene (B. breve-IL24) on head and neck tumor xenograft in mice. Briefly, B. breve transformants were obtained through electro-transformation. Bacteria-tumor-targeting ability were analyzed in vivo over different time points (1, 3 and 7 days post-bacteria injection). Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…In our previous study, we already verified that the strain B. breve possess an anti-tumor effect on HNSCC tumor-bearing model (Wang et al, 2017). Yet, the exact mechanism was not fully explored.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our previous study, we already verified that the strain B. breve possess an anti-tumor effect on HNSCC tumor-bearing model (Wang et al, 2017). Yet, the exact mechanism was not fully explored.…”
Section: Discussionmentioning
confidence: 64%
“…Bifidobacterium , which is one of the dominant early colonization bacteria in human intestinal tract, was proven to regulate immune development (Arboleya et al, 2012), immune modulation (Fanning et al, 2012), and to possess an anti-inflammation (Strisciuglio et al, 2015) and anticancer (Wang et al, 2017) activity. The immune response is stain-specific (Lopez et al, 2010) and one of the mechanisms driving the immune functions is regulated by bifido-EPS.…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus-mediated IL24 mRNA therapy could enhance the in vivo and in vitro antitumor effects of radiotherapy for NPC [ 20 , 21 ]. A study of Bifidobacterium as a carrier of the IL24 mRNA to treat HNSCC in mice showed that the recombinant strain Bifidobacterium breve -IL24 had a stronger ability to inhibit tumor growth and induce tumor cell apoptosis [ 19 ]. Although there is no suitable way to conduct clinical trials of the IL24 mRNA as a targeted therapy for HNSCC and its subgroups, the current studies suggest that the IL24 mRNA could be a potential treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that the IL24 mRNA is an underlying candidate for gene treatment of cancer through boosting apoptosis in many types of cancer cells [ 14 17 ]. IL24 has been reported to play vital roles in the inhibition of tumor growth and induction of tumor cell apoptosis in HNSCC cells [ 18 , 19 ]. Adenovirus-mediated IL24 mRNA therapy could also enhance the in vivo and in vitro antitumor effects of radiotherapy for NPC [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of bacterial targeting of tumors involved direct cross-linking of the bacteria to the delivery substance or recombination of genes and bacteria as an arch on a 'bacterial robot' to target the tumor [21][22][23]. However, effective delivery of nanomedicines to tumor cells is difficult because of the complex tumor microenvironments, resulting in poor and uneven perfusion, poor vascular permeability, and a high density of stromal cells, as well as increased interstitial pressure [24].…”
Section: Introductionmentioning
confidence: 99%